2017
DOI: 10.1016/j.hal.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Domoic acid in a marine pelagic food web: Exposure of southern right whales Eubalaena australis to domoic acid on the Península Valdés calving ground, Argentina

Abstract: The gulfs that surround Península Valdés (PV), Golfo Nuevo and Golfo San José in Argentina, are important calving grounds for the southern right whale Eubalaena australis. However, high calf mortality events in recent years could be associated with phycotoxin exposure. The present study evaluated the transfer of domoic acid (DA) from Pseudo-nitzschia spp., potential producers of DA, to living and dead right whales via zooplanktonic vectors, while the whales are on their calving ground at PV. Phytoplankton and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 67 publications
2
16
0
Order By: Relevance
“…In contrast, harvests have not been closed due to domoic acid, a neurotoxin produced by species of the diatom genus Pseudo‐nitzschia (the regulatory limit for domoic acid being 20 μg g –1 of mussel tissue). Although no cases of ASP events have been documented to date either in wildlife or in humans in the Northern Patagonian gulfs, previous research carried out in Golfo Nuevo and Golfo San José showed the presence of domoic acid in samples of phytoplankton and mesozooplankton (mostly calanoid copepods), as well as in fecal samples of whales ( Eubalaena australis ) collected at similar sites and on similar dates to those of the present study (D'Agostino et al ). These findings indicate that southern right whales are exposed to domoic acid through the ingestion of contaminated zooplankton, mainly copepods, while they remain in their calving grounds in these gulfs.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In contrast, harvests have not been closed due to domoic acid, a neurotoxin produced by species of the diatom genus Pseudo‐nitzschia (the regulatory limit for domoic acid being 20 μg g –1 of mussel tissue). Although no cases of ASP events have been documented to date either in wildlife or in humans in the Northern Patagonian gulfs, previous research carried out in Golfo Nuevo and Golfo San José showed the presence of domoic acid in samples of phytoplankton and mesozooplankton (mostly calanoid copepods), as well as in fecal samples of whales ( Eubalaena australis ) collected at similar sites and on similar dates to those of the present study (D'Agostino et al ). These findings indicate that southern right whales are exposed to domoic acid through the ingestion of contaminated zooplankton, mainly copepods, while they remain in their calving grounds in these gulfs.…”
Section: Introductionsupporting
confidence: 75%
“…Abundance (ind m –3 ) of potential vectors of phycotoxin and phycotoxin levels present in mezooplankton samples from Golfo Nuevo ( A ) and Golfo San José ( B ). Domoic acid (DA) data from June to December 2015 in Golfo Nuevo and July to November 2015 in Golfo San José were taken from D'Agostino et al (). C = N ‐sulfocarbamoyl toxins; GTX = gonyautoxins; PTX = pectenotoxins; SPX = spirolides; DTX = dinophysistoxins.…”
Section: Resultsmentioning
confidence: 99%
“…The area is especially important to the humpback whale (Megaptera novaeangliae) and the southern right whale (Eubalena australis). Both are dependent on the Antarctic region to feed on krill before the long fasting periods, which they spend calving at lower latitudes [34,35]. However, krill is an important vector for DA [15], and DA can cross the placental barrier of pregnant marine mammals [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, krill is an important vector for DA [15], and DA can cross the placental barrier of pregnant marine mammals [15]. This raises concern for the accumulation of DA in marine mammals in the Antarctic region [4,34,35]. Thus, toxigenic blooms of DA-producing diatoms have the potential to disturb a marine ecosystem, which is already susceptible to the effects of climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Diatoms of the genera Nitzschia and Pseudo-nitzschia produce a neurotoxin, domoic acid (DA), which can be transferred via copepods to higher food web levels (Leandro et al, 2010a;Tammilehto et al, 2012;D'Agostino et al, 2017) and intoxicate organisms such as seabirds, whales and seals (Fritz et al, 1992;Leandro et al, 2010b;Jensen et al, 2015). Domoic acid can also cause amnesic shellfish poisoning in humans (Quilliam and Wright, 1989;Landsberg, 2002).…”
mentioning
confidence: 99%